Cranial Cruciate Ligament Desmotomies in Sheep Resulting in Peroneus Tertius Injury - Peter J. Welsh; Crystal G. Collier; Holly M. Clement; Michael N. Vakula; Jeffrey B. Mason (Case Reports in Veterinary Medicine)
Surgical destabilization of the stifle joint via cranial cruciate ligament desmotomy (CCLD) is a routine procedure for the study of osteoarthritis (OA). Traditionally performed in rats, rabbits, cats, and dogs, CCLD in sheep provides an opportunity to study the pathology and treatment of joint instability in a species whose stifle better represents the equivalent human femorotibial joint. The surgical approaches for CCLD in sheep are variable and can result in inconsistent outcomes. Eight sheep underwent CCLD for use in a gene therapy study. We report this case in which six of the eight sheep were clinically diagnosed by pathognomonic signs and later confirmed by postmortem dissection, with injury of the peroneus tertius (PT) muscle. The PT plays a crucial role in the normal gait of large animals, including sheep. Injury to the PT results in failure of the reciprocal apparatus of the hind limb in which the hock can be extended during stifle flexion creating a varied gait and an indiscriminate increase in instability of the stifle and hock joints. Restricted movement postoperatively may provide decreased variability in surgical outcomes. Alternatively, increased stifle instability via CCLD coupled with PT transection or PT transection alone could potentially provide a superior model of stifle instability and OA development in sheep.